2011
DOI: 10.1002/hep.24597
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the patient diagnosis of primary biliary cirrhosis: Further evidence for an environmental component to etiology

Abstract: The etiology of primary biliary cirrhosis (PBC) is far from clear. Both genetic and environmental factors are likely to be involved. We have previously reported evidence of space-time clustering, suggesting that a transient environmental agent may be involved in etiology. To further examine whether a seasonally varying environmental agent may contribute to the etiology of PBC, we have analyzed seasonal variation with respect to month of diagnosis using population-based data from northeast England over a define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 24 publications
1
34
1
Order By: Relevance
“…This was the first study to find space-time clustering of this disease and suggests that transient environmental agents might play a role in the aetiology of this disease. Further analysis of this population-based cohort found marked seasonal variation in diagnoses of PBC, with a peak in June (McNally et al, 2011). This suggests the involvement of a seasonally varying agent occurring at different locations in the environment.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This was the first study to find space-time clustering of this disease and suggests that transient environmental agents might play a role in the aetiology of this disease. Further analysis of this population-based cohort found marked seasonal variation in diagnoses of PBC, with a peak in June (McNally et al, 2011). This suggests the involvement of a seasonally varying agent occurring at different locations in the environment.…”
Section: Introductionmentioning
confidence: 93%
“…The present study is concerned with the detection of irregular temporal distributions of cases of PBC, as opposed to regular seasonal patterns or space-time clustering as addressed previously (McNally et al, 2009(McNally et al, , 2011, or individual temporal clusters. A general irregular temporal distribution of cases that is not confined to one particular time period or period of each year is known as 'temporal clustering' (Muirhead et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…We read with great interest the article by McNally et al, 1 who reported the involvement of a seasonally varying environmental agent in the etiology of primary biliary cirrhosis (PBC), and who have reported previously that a transient environmental agent may be involved in the etiology using a space-time clustering method among cases of PBC in a defined geographical population of northeast England. 2 A combination of genetic predisposition and environmental factors are thought to contribute the etiology of PBC.…”
Section: Frequent Detection Of Immunoglobulin M Anti-herpes Simplex Vmentioning
confidence: 99%
“…Space-clustering occurs when there is an excess of cases of a given disease within a restricted geographical area, at a specified period of time. The study by McNally et al [54] suggests space-clustering of PBC which cannot be attributed to variations in population density. According to the authors, these findings are suggestive of a widespread but transient causative agent (such as a virus) in a localized geographical area, which is consistent with a short ‘lag time’ between exposure to a particular agent followed by diagnosis at a later date, or a longer but constant ‘lag time’ between exposure to the agent and subsequent diagnosis.…”
Section: Clusters Of Pbc and Infectious Triggersmentioning
confidence: 99%
“…Recent data from a group in Newcastle appears to characterize the contribution of environmental (likely infectious) agents in the pathogenesis of PBC in a cluster of patients. McNally et al [54] analyzed space-time clustering using population-based data from northeast England over a period from 1987 to 2003. Space-clustering occurs when there is an excess of cases of a given disease within a restricted geographical area, at a specified period of time.…”
Section: Clusters Of Pbc and Infectious Triggersmentioning
confidence: 99%